WEB DEVELOPMENT - SINGH, AARTI; ANIKESH, ANANYA (IJRDO -Journal of Computer Science Engineering, 2015)
The web-technology is going through major changes these years, both with respect to types of systems based on web-technology, organization of the development work, required approaches and competencies, etc. We must rethink the organization of the development work. This requires a deeper and coherent understanding of the nature of web-development. This paper presents findings from a field study undertaken in a web-development company.Web development is a broad term for the work involved in developing a web site for the Internet (World Wide Web) or an intranet (a private network). Web development can range from developing the simplest static single page of plain text to the most complex webbased internet applications, electronic businesses, and social network services. A more comprehensive list of tasks to which web development commonly refers, may include web design, web content development, client liaison, client-side/server-side scripting,web server and network security configuration, and e-commerce development. Among web professionals, "web development" usually refers to the main non-design aspects of building web sites: writing markup and coding.This paper focuses on web devlelpoment areas of web development future scope of web development